Comparison of clinically indicated replacement and routine replacement of peripheral intravenous catheters: A systematic review and meta-analysis of randomized controlled trials - Chen, Ching-Yi; Chen, Wang-Chun; Chen, Jung-Yueh; Lai, Chih-Cheng; Wei, Yu-Feng (Frontiers in Medicine, 2022)
Background: It is unknown whether clinically indicated replacement of peripheral intravenous catheters (PIVCs) increases the risks of PIVC-associated complications and infections compared to routine replacement of PIVCs. Methods: We searched PubMed, the Web of Science, the Cochrane Library, Ovid MEDLINE, and Clinicaltrials.gov for randomized controlled trials (RCTs) that compare the safety outcomes of routine replacement and clinically indicated replacement of PIVCs were included for meta-analysis. The primary outcome was the incidence of phlebitis, and secondary outcomes included the risks of occlusion, local infection, infiltration, catheter-related bloodstream infection (CRBSI), and accidental removal of the PIVC. Results: A total of 9 RCTs involving 10 973 patients were included in this meta-analysis, of whom 5546 and 5527 were assigned to the study group (clinically indicated replacement of PIVCs) and control group (routine replacement of PIVCs every 72-96 hours), respectively. The incidence of phlebitis in the study group was significantly higher than that in the control group (risk ratio [RR], 1.20; 95% confidence interval [CI], 1.01-1.44, P =.04, I2 = 49%). In addition, the study group was associated with a higher risk of occlusion (RR, 1.45; 95% CI, 1.08-1.95, P = .01, I2 = 82%) and infiltration (fluid leaks) (RR, 1.27; 95% CI, 1.06-1.53, P = .01, I2 = 72%) than the control group. However, no significant differences were observed in the risks of local infection (RR, 1.75; 95% CI, 0.38-8.16, P = .48, I2 = 0%) and CRBSI (RR, 0.61; 95% CI, 0.08-4.68, P = .64, I2 = 0%) between the study and control groups. Conclusions: The clinically indicated replacement of PIVCs may increase the risks of PIVC-associated phlebitis, infiltration, and occlusion compared to the routine replacement of PIVCs, but did not increase the risk of PIVC-associated infections. Based on these findings, routine replacement of PIVCs every 72-96 hours maybe a preferred option than clinically indicated replacement of PIVCs.